2016
DOI: 10.1080/10503307.2016.1208853
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic collaboration and the assimilation of problematic experiences in emotion-focused therapy for depression: Comparison of two cases

Abstract: Aims: The Assimilation model argues that therapists should work responsively within the client's therapeutic zone of proximal development (TZPD). This study analyzed the association between the collaborative processes assessed by the Therapeutic Collaboration Coding System (TCCS) and advances in assimilation, as assessed by the Assimilation of Problematic Experiences Scale (APES).Method: Sessions 1, 4, 8, 12, and 16 of two contrasting cases, Julia and Afonso (pseudonyms), drawn from a clinical trial of 16-sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
15
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 62 publications
7
15
0
6
Order By: Relevance
“…Regarding the present task of self-narrative reconstruction we can say that therapeutic activity appeared as a collaborative effort that was constant across the several steps of the model. This is congruent with the emotion-focused therapeutic stance, which has been evidenced in other studies with EFT for depression (e.g., Ribeiro et al, 2016). Moreover, several instances of dyadic interaction also evidenced tangential processes (defined as moments of dyadic activity appearing in the form of if-then contingent actions-if the client does X, then the therapist does Y; cf., Bennett et al, 2006) that become explicit at specific junctures of the therapeutic conversation.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Regarding the present task of self-narrative reconstruction we can say that therapeutic activity appeared as a collaborative effort that was constant across the several steps of the model. This is congruent with the emotion-focused therapeutic stance, which has been evidenced in other studies with EFT for depression (e.g., Ribeiro et al, 2016). Moreover, several instances of dyadic interaction also evidenced tangential processes (defined as moments of dyadic activity appearing in the form of if-then contingent actions-if the client does X, then the therapist does Y; cf., Bennett et al, 2006) that become explicit at specific junctures of the therapeutic conversation.…”
Section: Discussionsupporting
confidence: 84%
“…The study of these cases suggests that the therapeutic strategies are essentially related with a collaborative style from therapists characterized by non-directive, empathic, and exploratory interventions expected at this phase Greenberg, 1984Greenberg, , 1991Greenberg et al, 1993;Ribeiro et al, 2016). Furthermore, exploratory interventions have also been related to reconceptualization and performing change IMs in a previous study with this sample (Cunha, Gonçalves, Hill, et al, 2012), suggesting their key role in the productivity of EFT.…”
Section: Discussionmentioning
confidence: 77%
“…A series of intensive case studies of assimilation progress in different therapeutic models has shown that good outcome clients, as assessed by standard symptom intensity measures, progress toward high APES levels across their sessions (e.g., Brinegar, Salvi, & Stiles, 2008;Caro Gabalda, 2011;Caro Gabalda, Stiles, & Pérez Ruiz, 2016;Gray & Stiles, 2011;Honos-Webb, Stiles, & Greenberg, 2003;Knobloch, Endres, Stiles, & Silberschatz, 2001;Mendes et al, 2016;Osatuke et al, 2007;Ribeiro, Braga et al, 2016a;Ribeiro, Cunha et al, 2016b). For example, in a study of one good outcome client, Basto et al (2016) found a strong negative correlation across 16 sessions of CBT between APES level and symptom intensity.…”
Section: Relation Of Assimilation To Therapy Outcomementioning
confidence: 99%
“…The therapeutic ZPD may be different for each problem and will move as the client makes progress on the problem. In order to promote novelty and progress in the assimilation process the therapist may press the client higher within the ZPD, but if the client feels this movement as too risky (exceeding the ZPD), he or she will move back into a less challenging stage of assimilation (Ribeiro, Ribeiro, Gonçalves, Horvath, & Stiles, 2013;Ribeiro et al, 2015). Therapeutic work occurs within the therapeutic ZPD developed between client and therapist under joint collaboration.…”
Section: Setbacks In the Assimilation Of Problematic Experiencesmentioning
confidence: 99%